The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1517-86922014000100014
|View full text |Cite
|
Sign up to set email alerts
|

Influencia do indice de massa corporal no equilibrio e na configuracao plantar em obesos adultos

Abstract: RESUMOIntrodução: A obesidade é uma doença crônica degenerativa multifatorial que pode levar a alterações do sistema musculoesquelético, como mudança do centro de gravidade e sobrecarga mecânica sobre os membros inferiores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
2
0
4
Order By: Relevance
“…We observed that pregnant women, weighing up to 68 kg, did not present alterations in the variables related to dynamic postural balance and to those inherent to sit-up activity. This finding is supported by similar work performed with obese people, showing that there is a direct relationship between weight gain and decrease in postural stability (5) . The biomechanical alterations, due to the increase in body weight and growth of Note: VOLL, oscillation speed during the lateral-lateral displacement; CDLL, directional control during the lateral-lateral displacement.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We observed that pregnant women, weighing up to 68 kg, did not present alterations in the variables related to dynamic postural balance and to those inherent to sit-up activity. This finding is supported by similar work performed with obese people, showing that there is a direct relationship between weight gain and decrease in postural stability (5) . The biomechanical alterations, due to the increase in body weight and growth of Note: VOLL, oscillation speed during the lateral-lateral displacement; CDLL, directional control during the lateral-lateral displacement.…”
Section: Discussionsupporting
confidence: 78%
“…Anthropometric variables can influence motor strategies related to the maintenance of postural balance (6) . Although weight and body mass index are directly related to this body function, studies which are available in the literature have evaluated this relationship in specific groups such as obese (5) , elderly (10) and athletes. However, to date, no studies were found to assess the influence of anthropometric variables on the postural balance of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a mudança na distribuição da massa corporal altera a localização do centro de massa, havendo a necessidade de readequação do posicionamento de outros segmentos e, possivelmente, do equilíbrio postural, podendo levar ao prejuízo do controle motor (YI et al, 2014), uma vez que a manutenção do equilíbrio postural reflete em boa qualidade de vida, e também é fundamental para a realização de atividades da vida diária tornando as pessoas independentes, sendo as situações de desequilíbrio as responsáveis por quedas e riscos de lesões (CAETANO et al, 2014 Além disso, levar uma vida ativa apresenta muitos outros benefícios sociais e psicológicos, já que as populações fisicamente ativas tendem a viver mais tempo que populações inativas. De fato, os hábitos diários têm sido alterados devido a novas formas de entretenimento (televisão, internet, jogos de vídeo), e esta mudança tem coincidido com taxas crescentes de excesso de peso e de obesidade infantil.…”
Section: Lista De Abreviaturas E Siglasunclassified
“…Em alguns estudos o tempo de tela, uso de televisão e computador associaram-se significativamente ao ganho de peso, o que torna a adoção desse estilo de vida preocupante (VASCONCELLOS et al, 2013), visto que a obesidade infantil é considerada a pandemia do século XXI em diversos países do continente americano e europeu. No Brasil, uma em cada três crianças no Brasil está pesando mais do que deveria, com uma representatividade de 33,5% de sobrepeso ou obesidade entre a sua população infantil (YI et al, 2014).…”
Section: Lista De Abreviaturas E Siglasunclassified